Review Of The Internal Control System Of Raw Material Inventory In Pt. Indo Sukses Sentra Usaha - Lisa Arisa; Romadhon Romadhon; umroh umroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Politeknik Piksi Input Serang, 2022)
Purpose - This is where you explain ‘why’ you undertook this study. If you are presenting new or novel research, explain the problem that you have solved. If you are building upon previous research, briefly explain why you felt it was important to do so. This is your opportunity to let readers know why you chose to study this topic or problem and its relevance. Let them know what your key argument or main finding is Design/methodology/approach - This study uses a descriptive method according to sugiono is a method used to describe or analyze a research result but is not used to make broader conclusions . research was conducted or actual problems. The data collection was carried out by means of interviews, observation and documentation. Finding - The results showed that PT. Indo Sukses Sentra Usaha weak raw material inventory control through related functions, where each function has a big responsibility. As well as causing delays in achieving production targets. The raw material inventory control system in supporting the production process caused by raw material inventories that often experience vacancies so that they cannot be produced.. Originality - Inventory internal control is one of the important elements in cost control